The Effects of Diet Particle Size on Animals Performance - Goodband, Robert D.; Tokach, Mike D.; Nelssen, Jim L. (My University, 2002)
This publication examines the effects of diet particle size on animal performance specifically in swine and poultry diets.
MF2025_2002_05
Keywords: MF2050; Livestock; MF